Human skin explants an in vitro approach for assessing UVB induced damage - Khalil, Christian (2018)
Lifestyle changes involving frequent outdoor activities are contributing to higher exposure to harmful ultraviolet light (UVB). The acute effects of UVB irradiation on human skin was evaluated in this study using freshly excised human skin from elective surgery subjected to UVB doses (0–3.76 J/cm2). The assessment of UVB induced cellular and skin damages was undertaken at two time points immediately and 24 h post exposure using in vitro, and immunohistochemical staining techniques. The results indicated no significant loss of skin integrity or significant acute mitochondrial cellular damages in UVB exposed skin sections as measured by the MTS cytotoxicity assay. The other key markers of damage showed significant extracellular LDH membrane leakages and upregulation of inflammatory cytokines such as IL-1β. Skin integrity analysis was also undertaken using H&E, HLADR, and anti-cytokeratin antibodies. The results showed significant epidermal changes, basal cell activation and Langerhans cells depletion. The research proved the usefulness of freshly excised human skin explant model in measuring UVB damage. Furthermore, freshly excised human skin maintains the natural layering and therefore does not pose the same challenges faced by commercially available reconstructed skin in terms of higher costs and accurate mimicking of all the complex interactions observed in human skin.